Pengaruh Penggunaan Model Pembelajaran Inquiry Pada Mata Pelajaran Pendidikan Agama Islam Terhadap Keterampilan Berpikir Dan Kemandirian Belajar Peserta Didik Kelas VII Di SMPN Unggulan Sindang Kabupaten Indramayu - Lilah Kholilah (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
This study aims to provide proof of the description of the implementation of the inquiry learning model in Islamic learning at the Junior High School of Sindang, Indramayu Regency, to the skills of learning thinking and independence. This study uses a quasy-experimental method with the type of non equivalent post-test only control group design research design. Data collection techniques used questionnaire distribution techniques to 59 respondents consisting of 30 respondents in the experimental class and 29 respondents in the control class.The statistical analysis used was the independent t-test analysis. Based on the results of linear regression analysis, it was concluded that: The application of the inquiry learning model in Islamic learning was good. This can be seen from the average response of respondents in the experimental class) in the good category of 77.98%. 2) There is a difference in the average score of students' thinking skills with a value of t. positive count of 4.162, sig value. (2-tailed) of 0,000, and the mean difference of 5.552. 3) There are differences in the average score of learning independence with the value of t. positive count of 3.922, sig value. (2-tailed) of 0,000 and the mean difference of 6,268.Penelitian ini bertujuan untuk memberikan pembuktian tentang gambaran penerapan model pembelajaran inquiry pada mata pelajaran Pendidikan Agama Islam Kelas VII di junior high school Unggulan Sindang Kabupaten Indramayu, terhadap keterampilan berfikir dan kemandirian belajar. Penelitian ini menggunakan metode quasi eksperimen dengan jenis desain penelitian non equivalent post-test only control group design. Teknik pengumpulan data menggunakan teknik penyebaran angket kepada 59 responden terdiri atas 30 responden di kelas eksperimen dan 29 responden di kelas kontrol.Analisis statistik yang digunakan adalah analisis independent t-test. Berdasarkan hasil analisis regresi linear, disimpulkan bahwa: Penerapan model pembelajaran inquiry dalam pembelajaran PAI adalah baik. Hal ini dapat dilihat dari rata-rata jawaban responden di kelas eksperimen) dalam kategori baik sebesar 77,98%. 2) Terdapat perbedaan rata-rata skor keterampilan berpikir peserta didik dengan nilai t. hitung positif sebesar 4,162, nilai sig. (2-tailed) sebesar 0,000, dan mean difference sebesar 5,552. 3) Terdapat perbedaan rata-rata skor kemandirian belajar dengan nilai t. hitung positif sebesar 3,922, nilai sig. (2-tailed) sebesar 0,000 dan mean difference sebesar 6,268